Casting the net broader to confirm our imaginations: the long road to treating wasting disorders. Issue 6 (23rd November 2017) - von Haehling, Stephan
Abstract: Wasting embraces muscle and tissue wasting in sarcopenia and cachexia. This article describes recent advances in the field published in the Journal of Cachexia, Sarcopenia and Muscle concerning diagnostic tools, biomarker development, pathophysiology, and treatment. Studies discussed herein embrace those on sarcopenia and cachexia in heart failure, chronic obstructive pulmonary disease, and cancer including also animal models.